Acute brain infarction detected by CCT and stroke risk in patients with transient ischemic attack lasting <1 hour. (1st June 2014) - Al-Khaled, Mohamed; Rauch, Linus; Roessler, Florian; Eggers, Jürgen
Abstract : Background and purpose: This study aimed to determine the frequency and associated factors of acute brain infarction (ABI) detected by noncontrast cranial computed tomography (CCT) in patients with transient ischemic attack (TIA) of symptom duration <1 h and to investigate the association between evidence of ABI and short-term risk of stroke. Methods: During a 54-month period (starting November 2007), consecutive patients with TIA (symptom duration <1 h) admitted and imaged with CCT were prospectively evaluated. Adjusted logistic regression was used to estimate odds ratios (ORs). Results: Of 1021 patients (mean age, 74.5 ± 11 years; 52% female) with TIA (symptom duration <1 h) imaged with CCT at admission, 68 patients (6.7%; 95% CI, 5.3–8.3%) exhibited TIA-related ABI. Adjusted logistic regression showed that ABI was independently correlated with atrial fibrillation (AF) (OR, 3.3; 95% CI, 1.4–7.9; p = 0.006) and time between onset and CT assessment >6 h (OR, 2.5; 95% CI, 1.1–6.1; p = 0.034). During hospitalization (5 ± 3 d), 22 patients (2.2%; 95% CI, 1.4–3.1%) developed a stroke. Patients with ABI had higher stroke rates than those without (10.3% and 1.6%, respectively; p < 0.001). Adjusted logistic regression revealed that stroke risk was independently correlated with ABI (OR, 5.3; 95% CI, 1.8–15.0; p = 0.002) and AF (OR, 2.6; 95% CI, 1.1–6.4; p = 0.026). Conclusions: Detection of ABI by CCT in TIA patients with symptom duration <1 h may depend on timing of CCT assessment and presence of AF. Evidence of ABI indicates an elevated stroke risk during hospitalization.